2020
DOI: 10.1002/eqe.3327
|View full text |Cite
|
Sign up to set email alerts
|

Discussion of user‐defined parameters for recursive subspace identification: Application to seismic response of building structures

Abstract: Structural damage assessment under external loading, such as earthquake excitation, is an important issue in structural safety evaluation. In this regard, an appropriate data analysis and system identification technique is required to interpret the measured data and to identify the state of the structure. Generally, the recursive system identification algorithm is used. In this study, the recursive subspace identification algorithm based on the matrix inversion lemma algorithm with oblique projection technique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…As a result, multiplying the sampling interval and the window length results in the first identification time, which can be observed in the following figures. According to past studies [35,37,38], i is assigned to cover the fundamental period of the simulated frame; it is 1 s in this example.…”
Section: Tracking Results For Constant Stiffnessmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result, multiplying the sampling interval and the window length results in the first identification time, which can be observed in the following figures. According to past studies [35,37,38], i is assigned to cover the fundamental period of the simulated frame; it is 1 s in this example.…”
Section: Tracking Results For Constant Stiffnessmentioning
confidence: 99%
“…where L ij is different parts of the lower triangular matrix and Q ij is different parts of the orthogonal matrix from LQ decomposition. This approach is also known as "Multivariable Output-Error State sPace (MOESP)" and can be considered a time-efficient alternative for matrix projection [34,35]. Again, Γ i can be retrieved by repeating Equations ( 12)-( 14) and substituting O orth for O MOESP to identify the linear elastic system matrix, A.…”
Section: Stochastic Subspace Identification (Ssi)mentioning
confidence: 99%
See 1 more Smart Citation
“…Tree main streams are available: one is sophisticatedly derived via matrix inversion lemma [26,27,36,37], the other is accomplished by the cross-multiplication of matrices from QR decomposition [30,31,38,39], and the last one rotates the newest vector in QR decomposition to update the projection [28,29,40,41]. Some comparative studies of these two methods can be found in the literature [32][33][34][35]42]. Despite the success brought by those methods, the same procedure with SI produces inevitable decomposition steps.…”
Section: Implementation Of Recursive Subspace Identification (Rsi)mentioning
confidence: 99%
“…To enhance the efficiency of these original subspace approaches, an instrumental variable [34], a generalized Schur algorithm [35], empirical mode decomposition [36,37], a covariance-driven algorithm [38], and nuclear norm optimization [39] have been incorporated into subspace methods. To expand the application fields of subspace approaches from a time-invariant system to a time-variant system, the moving window technique [40,41] and recursive update algorithms [41][42][43][44][45] have been adopted.…”
Section: Introductionmentioning
confidence: 99%